2019
DOI: 10.1088/2053-1591/ab5fc8
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure changes responsible for the degradation of the 10CrMo9-10 and 13CrMo4-5 steels during long-term operation

Abstract: The paper presents results of microstructure and mechanical testing examinations performed using optical and transmission electron microscopy, tensile tests and Charpy tests on 10CrMo9-10 and 13CrMo4-5 steels, before and after they were long-term operated at elevated temperatures in a steam heater. In the 10CrMo9-10 steel, the optical microscopy detected a degradation of original bainite that was accompanied by the formation of ferrite, precipitates and micropores. The transmission electron microscopy revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…3a-b). On the other hand, the exploited material was characterized by degraded bainite, a small amount of ferrite and precipitated carbides concentrated at the grain boundaries [8] (Fig. 3c-d).…”
Section: Microstructural Analysis Of Damage Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…3a-b). On the other hand, the exploited material was characterized by degraded bainite, a small amount of ferrite and precipitated carbides concentrated at the grain boundaries [8] (Fig. 3c-d).…”
Section: Microstructural Analysis Of Damage Developmentmentioning
confidence: 99%
“…It was reported that the long-term operation of power engineering steels leads to significant changes in their microstructure which mainly include the diffusion of alloying elements out of the bainite, formation and coagulation of carbide precipitates at the grain boundaries, and partial transformation of original bainite to ferrite [8,15]. It was…”
Section: Microstructural Analysis Of Damage Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Small amounts of molybdenum (up to 0.35 wt.%) and chromium (up to 0.3 wt.%) provide heat resistance [9]. 13Cr (13CrMo4-5) is a higher-alloyed steel that contains up to 1 wt.% Cr and up to 0.6 wt.% Mo compared to 16Mo3 and has better oxidation and creep resistance [10].…”
Section: Introductionmentioning
confidence: 99%